2018
DOI: 10.3390/polym10080873
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Detection of Melamine Based on the Fluorescence Resonance Energy Transfer between Conjugated Polymer Nanoparticles and Gold Nanoparticles

Abstract: Adding melamine as additives in food products will lead to many diseases and even death. However, the present techniques of melamine detection require time-consuming steps, complicated procedures and expensive analytical apparatus. The fluorescent assay method was facile and highly sensitive. In this work, a fluorescence resonance energy transfer (FRET) system for melamine detection was constructed based on conjugated polymer nanoparticles (CPNs) and gold nanoparticles (AuNPs). The energy transfer efficiency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…The lower LoD of the MIP-QCM sensor systems proposed herein is two to three orders of magnitude higher, than those of previously published electrochemical [16,17] and optical [18,19,20] systems (low µM range vs. nM/tens of nM). On the other hand, the upper limit of detection is at the saturation concentration of melamine, i.e., 2.5 mM solution in water, which is much higher than for previously reported sensors.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The lower LoD of the MIP-QCM sensor systems proposed herein is two to three orders of magnitude higher, than those of previously published electrochemical [16,17] and optical [18,19,20] systems (low µM range vs. nM/tens of nM). On the other hand, the upper limit of detection is at the saturation concentration of melamine, i.e., 2.5 mM solution in water, which is much higher than for previously reported sensors.…”
Section: Resultsmentioning
confidence: 56%
“…Lu et al in 2017 compiled different methods for detecting melamine in food samples [15]. Biomimetic sensor systems proposed so far to detect melamine in milk and milk powders rely either on electrochemical approaches [16,17], or fluorescence/luminescence detection [18,19,20]. Furthermore, Li et al [21] came up with a continuous method to use DNA loops for continuously monitoring melamine in flowing milk via electrochemical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In the end of the last century, it was discovered that epoxy resins could be reinforced and toughened by the addition of a rigid thermoplastic phase of particles, thus the rigid-rigid polymer alloy concept was born [3]. The Iraqi Journal of Industrial Research (IJOIR) use of inorganic fillers of particles and reinforcement to modify the properties of polymers has been around for many years [4,5]. Jumahat et.al [6] found that the addition of nano-silica improved the tensile properties of the epoxy.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al obtained a novel fluorescent probe by FRET between gold and conjugated polymer nanoparticles. The probe was highly sensitive and selective to melamine and has been successfully applied to milk powder [22]. Sha et al designed a spirolactam rhodamine-linked adamantine as a ratiometric sensor for Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%